Pharmacist-Led Self-management Interventions to Improve Diabetes Outcomes. A Systematic Literature Review and Meta-Analysis - van Eikenhorst, Linda; Taxis, Katja; van Dijk, Liset; de Gier, Han (Frontiers in Pharmacology, 2017)
Background Treatment of diabetes requires a strict treatment scheme which demands patient self-management. Pharmacists are in a good position to provide self-management support. This review examines whether pharmacist-led interventions to support self-management in diabetes patients improve clinical and patient-reported outcomes. Methods This review was conducted according to the PRISMA guidelines. An extended literature search was conducted with the keywords “pharmacist”, “diabetes” and “self-management” using the electronic databases Pubmed, Embase, CINAHL, PsycINFO, Web of Science and the Cochrane Library from the beginning of the database through September 2017. In addition reference lists of systematic reviews and included studies were searched. Eligibility criteria included; self-management intervention tested with an RCT, performed in an ambulatory care setting, led by a pharmacist and reporting at least one clinical- or patient-reported outcome.. Primary outcomes were HbA1c (– as this is a clinical parameter for long-term diabetes follow-up), self-management and components of intervention. Secondary outcomes were blood glucose, blood pressure, BMI, lipids, adherence to medication, quality of life and diabetes knowledge. For the meta-analysis HbA1c values were pooled with a random-effects model in Revman 5.3. Risk of bias was assessed with the Cochrane Risk of Bias tool. Results Twenty-four studies representing 3,610 patients were included. Pharmacist-led self-management interventions included education on diabetes complications, medication, lifestyle and teaching of self-management skills. Some studies focused on patient needs through a tailored intervention. No key components for a successful self-management intervention could be identified. Pharmacist-led self-management interventions improve HbA1c levels with a mean of 0.71% (CI -0.91, -0.51; overall effect P < 0.0001) and had a positive effect on blood pressure (SBP -5.20 mm Hg [-7.58; -2.92], DBP -3.51 mmHg [-6.00; -1.01]), BMI (-0.49 kg/m² [-0.79; -0.19]), lipids (total cholesterol -0.19 mmol/l [-0.33; -0.05], LDL-C mmol/l -0.16 [-0.26; -0.06], HDL-C 0.32 mmol/l [0.02; 0.61]), self-management skill development and adherence to medication. Conclusion Pharmacist-led self-management interventions significantly improve HbA1c values in diabetes patients. These results underline the added value of pharmacists in patient-related care. Pharmacists should offer self-management support to diabetes patients in order to improve diabetes outcomes.